Adapting to Climate Challenges: Surviving at Fire and Post-Fire Debris/Mudflow Prone Zones in Colorado Front Range in Light of Feng-shui - Xu, Ping (Journal of Strategic Innovation and Sustainability, 2018)
Incorrect site selections can lead to disasters. Three pre-conditions for post-fire debris/ mudflows occurring in prone zones are: landforms trigger debris/mudflows; a wildfire strike has been experienced, accelerating and amplifying the debris/mudflow process; and constantly heavy rainfall is received. The high impact zones are where a sudden decline in slope appears in lower elevations, which causes the debris to release with the greatest impact; nearby rivers and lakes, that debris flows into and causes major flooding; and on hillsides with gullies pointing to or nearby the site. This interdisciplinary research would benefit site selection processes, warning criteria, and mitigation strategies.